Vitamin A intake is related to stress fracture occurrence in male collegiate long-distance runners - Toraishi, M.; Uenishi, K.; Iwamoto, J.; Otani, T. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Nutrient intake has an essential role in bone disorder prevention among long-distance runners. However, the influence of Vitamin A intake on the risk of stress fractures remains unknown. This prospective study aimed to investigate the association between Vitamin A intake, and stress fracture occurrence in male collegiate long-distance runners. METHODS: Forty-one male long-distance runners were recruited from a top-class long-distance college running team whose complete survey data on bone mass, anthropometric measurements, blood and urine tests, food intake frequency, history of competing in long-distance races, and monthly running distance during 2009-2010 were available. The influence of factors related to stress fractures, including Vitamin A intake, at baseline and the occurrence of stress fractures during the 1-year period were investigated. RESULTS: Four athletes experienced stress fractures during the study period (stress fracture group) and had significantly higher Vitamin A, calcium, and iron intake at baseline compared with that in the nonstress fracture group. In the stress fracture group, the mean daily Vitamin A intake was 2792 µg of retinol activity equivalents (RAE), which was higher than the upper intake limit for males aged 18-25 years in the Japanese Dietary Standard. Logistic regression analyses showed that only Vitamin A intake independently contributed to stress fracture occurrence. The odds ratio of developing stress fractures with a 100-µg RAE increase in Vitamin A intake was 1.22. CONCLUSIONS: A result of the present study suggested that Vitamin A intake was associated with stress fracture occurrence in male collegiate long-distance runners.